Environmental impacts of baby food: Ready-made porridge products. (1st March 2019) - Sieti, Natalia; Rivera, Ximena C. Schmidt; Stamford, Laurence; Azapagic, Adisa
Abstract: Scant information is available on the environmental impacts of baby food. Therefore, the aim of this work is to evaluate the life cycle environmental sustainability of one of the most common baby foods consumed for breakfast – ready-made porridge – and to identify options for improvements. Two variants of the product are considered: dry and wet porridge. The latter has from 43% to 23 times higher impacts than the dry alternative, with the global warming potential (GWP) of wet porridge being 2.6 times higher. However, the results are sensitive to the assumption on energy consumption for the manufacture of wet porridge, showing that reducing the amount of energy by 30% would reduce this difference by 5%–70% across the impacts. The main hotspots for both products are the raw materials and manufacturing; packaging is also significant for the wet option. For the dry porridge, product reformulation would reduce the environmental impacts by 1%–67%, including a 34% reduction in GWP. Reducing water content of the cereal mixture in dry porridge from 80% to 50% would reduce GWP of the manufacturing process by 65% and by 9% in the whole life cycle. Using a plastic pouch instead of a glass jar would decrease most environmental impacts of wet porridge by 7%–89%. The findings of this study will be of interest to both baby food producers and consumers. Graphical abstract: Highlights: Carbon footprint of wet porridge baby food is 2.6 times higher than dry porridge. Other environmental impacts of wet porridge are 43% to 23 times higher than dry. Raw materials and manufacturing are the main hotspots for both products. Product reformulation can reduce the impacts of dry porridge by up to 67%. Swapping glass jars for plastic pouches cuts the impacts of wet porridge by 7–89%.